Bagaimana Good Corporate Governance (GCG) dalam Keberlanjutan Perusahaan? - Kurniyati, K.; Khairiyani, K. (AKTSAR: Jurnal Akuntansi Syariah, 2020)
This research aimed to examine the effect of Good Corporate Governance (GCG) on firm value. Good Corporate Governance (GCG) was measured by the Corporate Governance Perception Index (CGPI). CGPI was assessed by the Indonesian Institute of Corporate Governance (IICG), an independent institute that was conducting the development of Good Corporate Governance in Indonesia. The firm value was reflected by the stock price, PBV (Price to Book Value), and Tobin’s Q. This study used ten firms as a sample consistently listed in the Indonesian Stock Exchange and followed the CGPI program during 2014-2019. The sample was determined by using purposive sampling. Analysis of data in this study used Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 3rd version. The result showed that CGPI reflected Good Corporate Governance affected firm value (stock price, PBV, and Tobin’s Q).